ANTIBACTERIAL EFFECTIVENESS OF Stenochlaena palustris LEAVES EXTRACT AGAINST THE GROWTH OF Streptococcus mutans - Mery Novita; I Wayan Arya Krishnawan Firdaus; Irham Taufiqurrahman (FKG Unlam, 2022)
Background: Dental caries is a common chronic infectious disease of dental hard tissue resulting from the interaction between tooth structure, the microbial biofilm formed on the tooth surface, dietary as well as salivary influences. Streptococcus mutans are considered to be the main bacteria that play role in the formation of cariogenic biofilms. Chlorhexidine gluconate 0,2% is a commonly used mouthwash and considered as the gold standard. The long-term use of chlorhexidine gluconate 0,2% may cause side effects so an alternative mouthwash with natural ingredients is needed. Kelakai leaves extract contains bioactive compounds which has antimicrobial effects such as flavonoids, alkaloids, tannins and saponins which can be used as an alternative mouthwash for chlorhexidine gluconate 0.2%. Objective: The purpose of this study was to observe the antibacterial effectiveness of kelakai leaves extract with concentrations of 3.125%, 6.25%, 12.5%, 25%, 50%, 75% and 100% with chlorhexidine gluconate 0.2% on growth of Streptococcus mutans bacteria. Methods: This study conducted through true experimental laboratories with a post-test only research design with control group design. This study used 9 treatments with 5 repetitions so that there were a total of 45 samples. The treatment group was kelakai leaves extract with concentrations of 3.125%, 6.25%, 12.5%, 25%, 50%, 75% and 100% with two control groups namely chlorhexidine gluconate 0.2% and distilled water against Streptococcus mutans. Results: The MIC of kelakai leaves extract was set at a concentration of 12.5% and the MBC at a concentration of 50%. Conclusion: Kelakai leaves extract concentrations 50%, 75% and 100% has antibacterial effectiveness which equivalent to chlorhexidine gluconate 0,2% against Streptococcus mutans bacteria.Keywords: Antibacterial, Stenochlaena palustris leaves extract, Streptococcus mutans